Perspectives on the future of dysmorphology. Issue 3 (9th December 2022) - Solomon, Benjamin D.; Adam, Margaret P.; Fong, Chin‐To; Girisha, Katta M.; Hall, Judith G.; Hurst, Anna C. E.; Krawitz, Peter M.; Moosa, Shahida; Phadke, Shubha R.; Tekendo‐Ngongang, Cedrik; Wenger, Tara L.
Abstract: The field of clinical genetics and genomics continues to evolve. In the past few decades, milestones like the initial sequencing of the human genome, dramatic changes in sequencing technologies, and the introduction of artificial intelligence, have upended the field and offered fascinating new insights. Though difficult to predict the precise paths the field will follow, rapid change may continue to be inevitable. Within genetics, the practice of dysmorphology, as defined by pioneering geneticist David W. Smith in the 1960s as "the study of, or general subject of abnormal development of tissue form" has also been affected by technological advances as well as more general trends in biomedicine. To address possibilities, potential, and perils regarding the future of dysmorphology, a group of clinical geneticists, representing different career stages, areas of focus, and geographic regions, have contributed to this piece by providing insights about how the practice of dysmorphology will develop over the next several decades.